2012
DOI: 10.1038/mi.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

IL-17-producing innate lymphoid cells are restricted to mucosal tissues and are depleted in SIV-infected macaques

Abstract: SUMMARY Innate lymphoid cells (ILCs) are an emerging subset of lymphocytes involved in surveillance against virally infected cells. Here we show CD3−CD8high lymphocytes in macaque blood include major subsets of ILCs including NK cells expressing CD16, NKp46 and NKG2A, but also populations of ILCs in mucosal tissues having different properties. One ILC subset secreted IL-17 (ILC17), but these were restricted to mucosal tissues. Some mucosal ILC17 cells expressed classical NK-cell markers, but little NKG2A or NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
117
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 66 publications
4
117
1
1
Order By: Relevance
“…It is reported that SIV infection results in a persistent loss of IL-17-producing ILCs, especially in the jejunum (21). Another report has indicated that NKp44 + Group 3 innate lymphoid cells (ILC3s) have demonstrated roles in promoting antibacterial immunity, maintaining epithelial barrier function, and supporting tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that SIV infection results in a persistent loss of IL-17-producing ILCs, especially in the jejunum (21). Another report has indicated that NKp44 + Group 3 innate lymphoid cells (ILC3s) have demonstrated roles in promoting antibacterial immunity, maintaining epithelial barrier function, and supporting tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: AhR, aryl hydrocarbon receptor; GALT, gutassociated lymphoid tissue; ILC, innate lymphoid cell; LTA, lipoteichoic acid; SIV, simian immunodeficiency virus; T h , T helper We and others have previously shown that CD3 2 CD8 high lymphocytes in the intestine represent a heterogeneous population including NK cells and other ILCs (2,23,24). In this study, we found that ILC3 subsets, defined by c-Kit + IL-7a + lineage-negative cells, are distinct from CD3 2 CD8 high cells, as indicated by ILC3 containing considerable CD3 2 CD8 2 cells (;70%) in macaques.…”
mentioning
confidence: 99%
“…29, 5072-5080 (2015). www.fasebj.org Key Words: SIV • HIV • GALT • ILC Innate lymphoid cells (ILCs) represent a phenotypically and functionally heterogeneous population of lymphocytes that has important roles in lymphoid tissue formation during embryonic and adult life, maintenance and protection of epithelial barriers against infection, regulation of adaptive immune responses, maintenance of gut-associated organized lymphoid tissue (GALT), and restoration of GALT following injury to mucosal barriers (1)(2)(3)(4)(5)(6)(7)(8). In contrast to T and B cells, ILCs do not express antigen-specific receptors.…”
mentioning
confidence: 99%
“…AIDS, CD, HCV associated hepatitis, Cystic fibrosis (CF) and Cancer etc.). ILC17 restricted to mucosal tissues were significantly lost in the jejunum during simian immunodeficiency virus (SIV) infection (29). These results indicate that loss of innate immune function mediated by ILC17 cells at mucosal surfaces may lead to disruption of intestinal mucosal immune system integrity and progression of HIV infection in humans or SIV infection in macaques.…”
Section: Fig 2 Role Ofilcs In Different Inflammatory Conditions Ofrmentioning
confidence: 73%